EFFECTS OF IRRIGATION AND FERTILIZATION ON STEM DIAMETER GROWTH IN A MEDITERRANEAN HELM OAK FOREST (FOREST ECOLOGY AND MANAGEMENT, 1994)
The effects of irrigation and fertilization on stem diameter growth are reported for helm oak (Quercus ilex L.), an evergreen tree that is a common dominant in Mediterranean forests. The experiment was conducted at Prades (northeastern Spain) in a helm oak stand with a high density of stems of resprout origin (($) over bar x = 18275 stems ha(-1)), a widespread stand structure in the abandoned coppices that cover extensive tracts of Mediterranean mountains. Mean annual rainfall is 580 mm. Eight treatments were used in each of three blocks, resulting from the factorial combination of: (i) irrigation at rates of about 20 mm week(-1) during three consecutive warm seasons; (ii) nitrogen fertilization in a single application of 250 kg N ha(-1); (iii) phosphorus fertilization in a single application of 125 kg P ha(-1). Stem diameters at 50 cm from the ground were measured before and 3 years after treatment application began. Stem diameter increments in control plots were very low (($) over bar x+/-SE 0.27+/-0.07 mm year(-1)), probably as a result of the high stand density and low water availability. Stem diameter growth was positively but loosely correlated with initial stem diameter. Irrigation significantly (P<0.01) increased mean stem diameter growth by 66%, but N and P fertilization did not. Surprisingly, there were no significant interactions between irrigation and fertilization, i.e. irrigated and fertilized trees did not grow significantly faster than irrigated-only trees. Effects of irrigation were larger on plots having lower initial basal area of helm oak. Irrigation increased stem diameter growth more in large trees than in smaller ones, thus enhancing the pre-existent inequalities in growth rates. Stem diameter growth in this high density stand is limited by water availability but has not responded to N or P additions during the first 3 years after fertilization.